Nevroprotektivno delovanje antibiotikov - Gaberc, Tjaša (Placebo, 2024)
Neurodegenerative diseases such as Alzheimer's, Parkinson's and multiple sclerosis pose a global challenge due to the chronic degeneration of neurons in the brain, which cause movement and cognitive disorders of patients. Despite extensive research, treatment is so far only symptomatic, but there are promising therapeutic options with antibiotics such as beta-lactams, tetracyclines, and rifampicin. These antibiotics can reduce disease progression through several pleiotropic effects, such as increase of glutamate transporter 1 expression, inhibition of apoptosis, mitochondrial damage, neuroinflammation, and reduction of protein aggregation. Unfortunately, some antibiotics have shown neurotoxicity at higher doses or after prolonged use, so further clinical safety research will be crucial to understand and exploit their therapeutic potential for treatment of neurodegenerative diseases.
Keywords: Antibiotiki; nevrodegeneracija; Nevrodegenerativne bolezni; nevroprotekcija; nevrovnetje